Proposta de melhoria do desempenho ambiental associado ao ciclo de vida da produção do painel de madeira MDF - Piekarski, Cassiano Moro (2013)
The present research aims to propose actions in order to improve the environmental performance associated with the MDF production life cycle, by means of Life Cycle Assessment (LCA) application. This study was conducted following the guidelines of regulatory standards ISO 14040 and 14044. In order to calculations procedures and panel production scenarios modeling was used the Umberto® software v.5.6, with the life cycle inventory database entitled Ecoinvent v.2.2. The actions proposed in order to improve the environmental performance of the MDF production were formulated based on the LCA results. Faced with these peculiarities, was constructed the Life Cycle Inventory (LCI) for MDF production, under the Brazilian production chains conditions. Based on LCI data, was evaluated the impacts of panel production life cycle by the methods CML (2001), EDIP (1997) and USEtox (2008). The categories of impacts assessed were: acidification potential, global warming, ozone layer depletion, abiotic resource depletion, photochemical formation of tropospheric ozone, ecotoxicity, eutrophication and human toxicity. The results showed six potential contributors to impacts categories (hotspots): consumption of natural gas in the thermal plant, resin UF (urea formaldehyde), electricity consumption, consumption of wood waste in thermal plant, consumption of wood chips, and transportation of wood chips to industry. According to the hotspots identified were formulated actions in order to improve the environmental performance of the product. The actions were sensitively analyzed in different scenarios in order to verify the effectiveness in reducing potential impacts. The proposal for improving the environmental performance was included the following actions: extinction of natural gas used in the thermal plant, proportional reduction of wood fuel that not have been chemically treated, accomplish specialized analysis to check the efficiency of combustion in thermal plant, reduction the electricity consumption, reduction of resin UF consumption, reduction of wood consumption and minimize the distances of wood suppliers. As regards the sensitive analysis of alternative scenarios that can incorporate the proposal, we highlight the fact that the extinction of natural gas consumption in the thermal plant can reduce approximately 30% of the potential impacts of depletion of resources abiotic and ozone layer. The proposal presented in this research subsidizes and guides sustainable strategic actions that, by virtue of being evaluated on a life cycle approach, are not only limited to the production process or a single operational activity.